EXPLORING LOCAL VALUES AND CULTURE IN ENGLISH TEXTBOOK - Cahyati, Sri Supiah; Rahmijati, Cynantia (Lingual Journal of Language and Culture; Vol 4 No 2 (2017), 2017)
The purposes of this research, entitled "Exploring Local Values and Culture in English Textbook", are to identify and analyze the local values & culture in 8 English textbooks for high school level; to elaborate the scope of the values in English textbooks for high school level. The method used is a qualitative descriptive method.The results show that in the 8 English textbooks all contain local value and culture, they are value of religion, customs, governance/social, procedures, textual, buildings and religious values whereas the scopes of the values are traditional and modern values. Keywords: local values, English textbooks